The Role of Investment in Road Development in Egypt - Elgazzar, Yasmine Mahmoud (Journal of Economic, Administrative and Legal Sciences, 2019)
The paper illustrates the role of investment in the roads transportation sector development in Egypt. As the investments is considered an important source of external funding especially for countries that are characterized by low level of savings and investments like Egypt. As the country is seeking to attract many investments in order to work on the expansion and the construction of new urban communities and industrial centers. Egypt also is trying work on extending the roads networks between the different regions. The thing that made it a necessity for Egypt to attract the private investment sector as source to finance these investments in the transportation sector. To achieve the objective of the paper, both inductive and descriptive analytical approaches will be combined. The study concluded that there should be integration between economic activity plans and expansion plans in transport activities depending on the size of investment and also encourage the private sector to provide many investments to help the growth of industries, intensify investment and participate in the wheel of economic development.
Keywords: land transport; public sector; private sector; economic development; infrastructure; investment; partnership between the public and private sectors